Prediction of Lateral Instability and Reducing Rearward Amplification of Autonomous Long Combination Vehicles - Esmaili, Henrik (My University, 2020)
Autonomously driven long combination vehicles have potential advantages such as higher levels of safety, greater fuel efficiency and reduced total cost of ownership per ton of unit freight. On the other hand, long combination vehicles are more prone to lateral instability such as trailer swinging. In addition, lateral instability is far more difficult to control compared to shorter combinations. This thesis presents an intuitive and simple controller, designed for an autonomous highway driving A-double. The controller is developed to both reduce lateral instability and the rearward amplification that a vehicle generates during a typical highway lane change and step-steer manouvre. A linear single-track model of an A-double was employed as a foundation for the controller. The linear single-track model was verified against a simulation model and data from real testing of an A-double. The performance of the controller was tested for different manoeuvres as well as compared against the uncontrolled case, a band-stop filter and a low-pass filter. The results showed that the controller reduced rearward amplification for all manoeuvres. However, open-loop and closed-loop testing of the controller in simulation is necessary before any real testing is conducted.
Keywords: Long combination vehicles; Autonomous driving; Lateral instability; Rearward amplification; Control method